Content applicability in Facebook: The case of banks operating in Lithuania - Kazlauskaitė, Kristina (Information & Media, 2017)
The aim of this article is to analyze the peculiarities of content marketing and to state content applicability in bank communication in social media. In the theoretical part of this article, we are reviewing the concept of content marketing, its types and features. The empirical part of this article identifies content marketing usage in bank communication on Facebook. Research was carried out by using these methods: qualitative and quantitative content analysis, observation, summarizing and comparison. It was discovered that banks use content marketing in their communication on Facebook. The main types of content were distinguished – photos, links, text and analyzed customer’s feedback, their reactions to the submitted content and cooperation. The insights of this article can be beneficial for businesses and organizations that implement content marketing processes in their communication on social media.